Studies in fractional poisson measures - Silva, José Luís da (2012)
In this paper we investigate the quasi-invariance property of fractional Poisson measures with respect to the diffeomorphism subgroup and we construct spaces of test and generalized functions associated to the corresponding fractional Lebesgue-Poisson measures.